KMT5B is required for early motor development - Hulen, Jason; Kenny, Dorothy; Black, Rebecca; Hallgren, Jodi; Hammond, Kelley G.; Bredahl, Eric C.; Wickramasekara, Rochelle N.; Abel, Peter W.; Stessman, Holly A. F. (Frontiers in Genetics, 2022)
Disruptive variants in lysine methyl transferase 5B (KMT5B/SUV4-20H1) have been identified as likely-pathogenic among humans with neurodevelopmental phenotypes including motor deficits (i.e., hypotonia and motor delay). However, the role that this enzyme plays in early motor development is largely unknown. Using a Kmt5b gene trap mouse model, we assessed neuromuscular strength, skeletal muscle weight (i.e., muscle mass), neuromuscular junction (NMJ) structure, and myofiber type, size, and distribution. Tests were performed over developmental time (postnatal days 17 and 44) to represent postnatal versus adult structures in slow- and fast-twitch muscle types. Prior to the onset of puberty, slow-twitch muscle weight was significantly reduced in heterozygous compared to wild-type males but not females. At the young adult stage, we identified decreased neuromuscular strength, decreased skeletal muscle weights (both slow- and fast-twitch), increased NMJ fragmentation (in slow-twitch muscle), and smaller myofibers in both sexes. We conclude that Kmt5b haploinsufficiency results in a skeletal muscle developmental deficit causing reduced muscle mass and body weight.